Pengaruh Komunikasi Interpersonal, Kepemimpinan Transformasional dan Komitmen Organisasi Terhadap Kinerja Pengurus PMII Rayon Al-Farabi - Hofifatul Musyarrofah; Eka Farida; M. Khoirul Anwarudin Broto Suharto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study’s goal was to ascertain the impact of interpersonal communication, transformational leadership and organizational commitment on the performance of PMII Rayon Al-Farabi. The study’s methodology is explanatory research with a quantitative approach. 63 respondents made up the sample in this study, which used the proportionate random sampling method. The results showed that the results of the F test of interpersonal communication, transformational leadership and organizational commitment simultaneously had a significant effect on performance. From the results of the t-test analysis, it is known that the interpersonal communication variable has a significant effect on performance and transformational leadership and organizational commitment variable has not significant effect on performance. Keywords: Interpersonal Communication, Transformational Leadership, Organizational Commitment and Performance